2022
DOI: 10.1002/cl2.1273
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Criminal justice interventions for preventing terrorism and radicalisation: An evidence and gap map

Abstract: This is the protocol for a Campbell systematic review. The objectives are as follows:to identify the existing evidence that considers the effectiveness of criminal justice interventions in preventing terrorism and radicalisation and to identify existing gaps in the evidence where new primary research could be undertaken and where future synthesis could be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The search for the EGM (Sydes et al, 2023) was extensive: nearly 70,000 unique records, which, after screening were reduced to 67 studies eligible for the EGM (from 58 documents). These included 2 systematic reviews, 14 randomised controlled trials and 51 quasi‐experimental studies.…”
Section: The Evidence and Gap Map (Egm)mentioning
confidence: 99%
“…The search for the EGM (Sydes et al, 2023) was extensive: nearly 70,000 unique records, which, after screening were reduced to 67 studies eligible for the EGM (from 58 documents). These included 2 systematic reviews, 14 randomised controlled trials and 51 quasi‐experimental studies.…”
Section: The Evidence and Gap Map (Egm)mentioning
confidence: 99%
“…However, our pilot screening for the EGM discovered studies addressing bio-terrorism (see Green, LeDuc, Cohen, & Franz, 2019; and cyber-terrorism (see . These were two categories of counterterrorism interventions we did not anticipate coding for in the protocol (see Sydes et al, 2022). As such, we made an early decision to alter the protocol coding scheme to include interventions that targeted bio-and cyber-terrorism.…”
Section: Types Of Intervention/problemmentioning
confidence: 99%
“…Exclusion criterion 3 was used to produce a corpus of studies that reported on quantitative impact evaluations of an eligible intervention, using an eligible research design. Exclusion criterion 3 deviated from the exclusion criteria outlined in the protocol (Sydes et al, 2022). The original exclusion criteria stated that the 'document does not include an impact evaluation of a criminal justice intervention that aims to prevent or respond to radicalisation/violent extremism/terrorism.'…”
Section: Gpd Sourced Documentsmentioning
confidence: 99%